Prinsip Kepemimpinan Umat Allah: Suatu Studi Terhadap Kepemimpinan Ezra - Shendy Carolina Lumintang (EUANGGELION: Jurnal Teologi dan Pendidikan Kristen, 2022)
This article aims to determine the leadership and leadership principles of God's people today based on Ezra's leadership principles. To achieve this goal, the author uses a qualitative approach and content analysis method, analyzing the messages conveyed through the primary and secondary literature regarding the focus of the discussion. The results show that there is a dualism in the leaders of God's people today by the development of the world. The dualism of the leader of God's people, among others, is because of a broken relationship with God, relativizing the truth, an ineffective role, a life motivation that is not in accordance with God's will, individual or egocentric attitudes, and regeneration problems. Based on Ezra's leadership, the leadership principles of God's people are having a foundation, depending on God (theocentric), being obedient and loyal to God's call, and being diligent in carrying out the duties and responsibilities as a leader. Thus, the leader of God's people he wants, namely the leader who returns to the statutes and the Word of God in all aspects of life, including his leadership.